Secrets of the seashore - Brown, Carron; Nassner, Alyssa (Tulsa, OK : Kane Miller, 2014)
Who lives at the seashore? Shine a light behind the page and see ... Explore a tidal pool up close and you will find a small world filled with great surprises! From jewel-like sea anemones to spiky sea urchins, the hidden wonders of this amazing habitat will be revealed.
Keywords: Seashore ecology -- Juvenile literature; Toy and moveable books